Effects of Psychiatric Disorders on Labor Market Outcomes: A Latent Variable Approach Using Multiple clinical Indicators - Souvik Banerjee; Pinka Chatterji; Kajal Lahiri (Center for Economic Studies and ifo Institute (CESifo), 2013)
In this paper, we estimate the effect of psychiatric disorders on labor market outcomes using a structural equation model with a latent index for mental illness, an approach that acknowledges the continuous nature of psychiatric disability. We also address the potential endogeneity of mental illness using covariance instruments as suggested in Lewbel (2012), thus not requiring questionable exclusion restrictions for identification. Data come from the US National Comorbidity Survey - Replication (NCS-R) and the National Latino and Asian American Study (NLAAS). We find that depression and generalized anxiety disorder detract from the employment and labor force participation of males and females; however, we do not find evidence of adverse effects of panic attack or social phobia on any work outcomes of either males or females. After addressing the potential endogeneity of mental illness, we continue to find that mental illness adversely affects employment and labor force participation for both males and females, but the effect on weeks worked and days missed at work are significant for males only. Using our structural model we assess the policy implications of some of the recommendations in the Affordable Care Act, relating to expansion of benefits for mental health and substance use disorder benefits. We find potential gains in employment for 3.2 million individuals and reduction in workplace cost of absenteeism of 18.9 billion due to improved mental health of individuals who are in most need of treatment.
Keywords: I10; 330; mental illness; labor market outcomes; depression; employment